PHYSICAL EXERCISE AS A NON-PHARMACOLOGICAL AID IN THE TREATMENT OF ANXIETY DISORDER. - OLIVEIRA JUSTO, ALBERTO FERNANDO; LUCIANO AFONSO, MARIANA; LUCIANO AFONSO, PEDRO PAULO (Brazilian Journal of Surgery & Clinical Research)
Anxiolytics such as with selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, and benzodiazepines are often used to treat anxiety disorders. However, up to a third of patients do not respond to them, and they can have side effects. Regular physical activity, on the other hand, can improve cardiovascular, urinary, and brain functions. Exercise increases nitric oxide production in endothelial cells, relaxes smooth muscle cells, inhibits platelets, and lowers low-density lipoprotein while increasing high-density lipoprotein. It also increases dopamine receptor affinity, leading to anxiolytic effects, and may link to noradrenaline levels in the brain, which also have anxiolytic effects. Exercise intensity can also regulate neurotransmitter release in the brain, which may have a role in anxiety. Meta-analyses and systematic reviews show the benefits of physical activity in treating anxiety disorders. Practicing physical activity reduces anxiety scores compared to sedentary individuals. Physical activity regulates anxiety through systemic and intracellular pathways, making it a potential alternative or complementary strategy for treating anxiety disorders. It has multiple benefits for both physical and mental health and has fewer side effects than anxiolytics.